Opposing Roles for CD34 in B16 Melanoma Tumor Growth Alter Early Stage Vasculature and Late Stage Immune Cell Infiltration - Maltby, Steven (Public Library of Science, 2011)
Tumor growth and metastasis are determined by the complex interplay of factors, including those intrinsic to tumor cells and extrinsic factors associated with the tumor microenvironment. Our previous work demonstrated key roles for CD34 in the maintenance of vascular integrity and eosinophil and mast cell homing. Since both of these functions affect tumor development, we characterized the effect of CD34 ablation on tumor growth using the B16F1 melanoma model. Intriguingly, we found that CD34 plays a biphasic role in tumor progression. In early growth, both subcutaneous-injected tumors and intravenous-injected lung metastases grew more slowly in Cd34(−/−) mice. This correlated with abnormal vessel morphology and increased vascular permeability in these mice. Bone marrow transplantation experiments confirmed that this reflects a non-hematopoietic function of CD34. At later stages, subcutaneous tumor growth was accelerated in Cd34(−/−) mice and surpassed growth in wildtype mice. Bone marrow chimera experiments demonstrated this difference was due to a hematopoietic function for CD34 and, correspondingly we found reduced intra-tumor mast cell numbers in Cd34(−/−) mice. In aggregate, our analysis reveals a novel role for CD34 in both early and late tumor growth and provides novel insights into the role of the tumor microenvironment in tumor progression.